Análise da integridade tissular de pacientes com o pé diabético - GONTIJO, Paula Vitória Costa (2019)
This study aimed to analyze the lower limb tissue integrity of patients with diabetic foot. This is a cross-sectional study with an analytical approach conducted from November 2018 to July 2019 at the diabetic foot outpatient clinic, located at the Empress Medical Center, with patients who were being followed up because of the need for diabetic foot treatment. . One hundred and thirty-four patients diagnosed with Diabetes Mellitus type 2 with diabetic foot who had only had a bandage and were 18 years old or older. For data collection, the instruments proposed by Santos (2011) and Silva (2014) were adapted. The interview and physical examination form contained 19 nursing outcome indicators tissue integrity: skin and mucous membranes, and five complementary indicators (edema, right and left dorsalis pulses, and right and left tibials) that, although not part of the result in nursing, consist of important information to assess skin integrity. These indicators are assessed using the five-point Likert scale. For univariate descriptive analysis, relative and absolute frequency measurements were presented. The means of the indicators were compared taking into account sociodemographic and clinical variables using the nonparametric Wilcoxon-Mann-Whitneye U test of Kruskal-Wallis. The results showed that the indicators with the lowest average score were skin temperature, perspiration, skin lesions, right and left pedis pulses, and right and left tibial pulses. All other indicators used to assess tissue integrity showed some degree of impairment ranging from mild to severe. It was also verified that there was a difference in the mean score of the indicator thickness and growth of skin hair in relation to gender and indicators of growth of skin hair, tissue integrity, skin lesions, hardening and right pedial pulse in relation to age. of the patients. Regarding family income, the indicators hydration, skin growth and abnormal pigmentation showed differences in the means between patients who received up to two minimum wages. Regarding the clinical variables, patients with chronic diseases had lower mean score in the right pedial pulse indicator and those who had no other associated disease had lower mean thickness, tissue integrity, skin lesions, scar tissue and erythema indicators. In addition, it was observed that the mean score of the sensation, tissue integrity, elasticity, thickness, right pedis pulse and right tibial pulse indicators varied according to the time of diagnosis of the disease. Among the diabetic foot types, the neuroischemic foot was the one that presented lower means in the indicators sensation, tissue perfusion, abnormal pigmentation, paleness, right and left pedis pulse and right and left tibial pulse, when compared to the other types. Given the above, it was identified that the sociodemographic, clinical variables and the neuroischemic diabetic foot influenced the level of impairment of the indicators, contributing to the occurrence of lower averages. From this information, nursing can support care using a standardized language, which allows assessing which characteristics of the diabetic foot are most affected.